ANALISIS PERBANDINGAN BIAYA MATERIAL BAJA DAN MATERIAL BETON PADA PEMBANGUNAN MALL PELAYANAN PUBLIK DIJALAN ELTARI KECAMATAN ALOK KABUPATEN SIKKA - Yohana Ema Muda; Triapriono Kaidu (Program Studi Teknik Sipil, 2024)
Reinforced concrete plays a scurecal role in the construction industry. The primary components of concrete are cement,fine aggregate (sand),coarse aggregate (gravel), and water,with the potential addition of chemical additives to enhance its uality.On the other hand, steel stuctures are excellent for earthuake resistance due to the material’s superior strength and ductility compared to otherstructural materials like concrete.The purpose of this research is to determine the budget for reinforced concrete structures, compare the costs between steel and reinforced concrete construction, and evaluate the cost difference between steel and reinforced concrete sctructures. The public service mall project data indicates that a steel structure was used.The results of the cost comparison showed that steel sctructures are more economical. The cost for the existing steel constuction was 1.390.830.035,73, while the cost for concrete concstruction was 1.572.927.091,00 , resulting in a cost difference of 182.092.055,27.Reason :1. Because rein forced concrete structures have many materials such as cement, sand and gravel and various additional materials.The large number of materials and long assembly results in high construction costs. 2. Because in the planning of the reinforcement of the first and second floors and the roof top of thr slab from the beams and columns for the main reinforcement and stirrup reinforcement/beugel I use the some dimensions,namely for the main reinforcement I use iron Ø16 and stirrup reinforcement Ø10